The moderating role of gender on the relationship between family environment and emotional intelligence - Naghavi, Fataneh; Redzuan, Ma'rof (Marsland Press, 2012)
Although a bulk of literature indicates that family environment influence emotional intelligence, the gender of early adolescents as one of the important determinants which buffers this effect received little empirical attention. The current study investigated the moderating role of gender on the relationships between family environment and emotional intelligence among 234 early adolescents (female and male) in grades 2 and 3 of guidance schools of Tehran, Iran. Data were collected using the Emotional Quotient Inventory Youth Version (Bar- on EQ-i; YV, 2000) and the Moos & Moos Family Environment Scale. Results revealed that family environment fostered emotional intelligence in their early adolescents. Furthermore, the findings demonstrated that gender moderated the relationship between family environment and emotional intelligence. Specifically, male respondents had tended to indicate more emotional intelligence than female respondents at higher levels of family environment. These findings underscore the need for continued focus on the role of parenting style when assessing the links between family environment and early adolescent’s emotional intelligence.